Trauma exposure and post-traumatic stress disorder among youth in a high-risk family study: Associations with maternal and paternal alcohol use disorder. Issue 2 (2nd April 2020) - Bender, Annah K.; Bucholz, Kathleen K.; Edenberg, Howard J.; Kramer, John R.; Anokhin, Andrey P.; Meyers, Jacquelyn L.; Kuperman, Samuel; Hesselbrock, Victor; Hesselbrock, Michie; McCutcheon, Vivia V.
Abstract: This study presents findings regarding the prevalence of trauma exposure and Posttraumatic Stress Disorder (PTSD) based on discrete types of trauma (physical, sexual, witnessed violence, and non-assaultive trauma) among 3404 youth in a family study of Alcohol Use Disorder (AUD). Data from the Collaborative Study on the Genetics of Alcoholism (COGA) were used to examine associations of parent AUD with offspring's childhood trauma exposure, and with lifetime diagnosis of DSM-IV PTSD among White and Black participants aged 12-35. Of 3404 youth, 59.7% had parents affected by AUD and 78% experienced ≤1 traumatic event before age 18. AUD in one or both parents was associated with physical, sexual, and witnessed violence among Whites. Among African Americans, maternal AUD was associated with sexual assault. The lifetime PTSD rate among youth exposed to childhood trauma was 8.6%, and mother-only AUD was significantly associated with lifetime PTSD among participants in both groups. PTSD among youth in this study were somewhat higher (7.9% to 8.83%) than those found in general population studies of the same demographic (5% to 6.8%). Maternal AUD appears to be a salient risk factor for sexual assault before age 18 among Black and development of lifetime PTSD among White youth.